Conditioning the visual system: A practical perspective on visual conditioning in rugby football - Meir, R. (Strength and Conditioning Journal, 2005)
Most team sports spend a considerable amount of time devoted to the physical and skill development of players.Fundamental to this process is the involvement of the visual system, and yet rarely do we hear of this quality being catered for within the strength and conditioning program. This article outlines some of the concepts associated with visual training as applied in the sports conditioning program at Gloucester Rugby Football Club in England.